Interbank Liquidity Crunch and the Firm Credit Crunch: Evidence from the 2007-2009 Crisis - Rajkamal Iyer; Samuel Da-Rocha-Lopes; José-Luis Peydró; Antoinette Schoar (Review of Financial Studies, 2014)
We study the credit supply effects of the unexpected freeze of the European interbank market, using exhaustive Portuguese loan-level data. We find that banks that rely more on interbank borrowing before the crisis decrease their credit supply more during the crisis. The credit supply reduction is stronger for firms that are smaller, with weaker banking relationships. Small firms cannot compensate the credit crunch with other sources of debt. Furthermore, the impact of illiquidity on the credit crunch is stronger for less solvent banks. Finally, there are no overall positive effects of central bank liquidity, but higher hoarding of liquidity.
Keywords: G01; G21; G28; G32; 330; credit crunch; banking crisis; interbank markets; access to credit; flight to quality; lender of last resort; liquidity hoarding